Policing Pleasure : Sex Work, Policy, and the State in Global Perspective. - Dewey, Susan; Kelly, Patty, 1968- (NYU Press, 2011)
Monica waits in the Anti-Venereal Medical Service of the Zona Galactica, the legal, state-run brothel where she works in Tuxtla Gutierrez, Mexico. Surrounded by other sex workers, she clutches the Sanitary Control Card that deems her registered with the city, disease-free, and able to work. On the other side of the world, Min stands singing karaoke with one of her regular clients, warily eyeing the door lest a raid by the anti-trafficking Public Security Bureau disrupt their evening by placing one or both of them in jail. Whether in Mexico or China, sex work-related public policy varies consid.